ANALYSIS OF AGRICULTURAL PRACTICES USED BY CEREAL FARMERS TO ADOPT TO PHENOMENON OF CLIMATR VARIATION IN THE GOVERNORATES OF THE CENTRAL REGION OF IRAQ - A. A. M. Al-Tamimi,; A. A. N. Al-Badri, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to identify the obstacles that facing cereal farmers that applying the agricultural practices to decrease the effects of climate variation phenomenon in the central region of Iraq. This research was conducted on cereal farmers at Baghdad, Najaf, Babil, and Wasit which were the most cultivated governorates of cereal crops (wheat, rice, and yellow corn). A randomized sample of (227) farmers was taken, that represents 0.25% of the total cereal farmers in the four governorates (90,584 farmers). In order to achieve the research goal, a questionnaire was prepared to collect data related to the research topic, for which a four-way scale was designed (33) paragraphs, and this field included three axes (1. Obstacles related to the farmers), (2. Obstacles related to the extension aspect), (3. Obstacles related to government institutions). The research concluded that the cereal farmers had a lack of knowledge about the effects of the climate variations phenomenon on their crops in the central region of Iraq, they also facing many obstacles that need to be solved, which led to their failure to use the correct agricultural practices.The research recommends the necessity of training farmers about scientific practices, research also recommends the necessity of holding training courses by the Agricultural Extension Organization for cereal farmers in order to increase their knowledge and develop their expertise in dealing with the climate variation phenomenon to advance the agricultural reality.